La calidad del sistema universitario en China: la Liga C9 y la clasificación de Shanghái - Ruiz Morillas, Nuria (El Colegio de México, 2019)
The Chinese university system has experienced significant growth in recent years. The government has allocated resources to boost research and increase the presence of Chinese universities on the world university map. Nine of these universities constitute the C9 League. In this paper, we analyze the evolution of positions in the Shanghai ranking of C9 League universities. We also compare these results with two other international classifications, the QS World University Rankings and Times Higher Education.